Safety and efficacy of tirofiban in acute ischemic stroke due to tandem lesions undergoing mechanical thrombectomy: A multicenter randomized clinical trial (ATILA) protocol. (March 2023) - Medina-Rodríguez, Manuel; Moniche, Francisco; de Albóniga-Chindurza, Asier; Ortega-Quintanilla, Joaquin; Ainz-Gómez, Leire; Pardo-Galiana, Blanca; Cabezas-Rodríguez, Juan Antonio; Aguilar-Pérez, Marta; Zamora, Aynara; Delgado-Acosta, Fernando; Jiménez-Gómez, Elvira; Bravo Rey, Isabel; et al.
Background: In-stent thrombosis after mechanical thrombectomy (MT) worsen outcomes in acute ischemic stroke (AIS) due to tandem lesions (TL). Although an optimal antiplatelet therapy is needed, the best approach to avoid in-stent thrombosis is yet to be elucidated. Hypothesis: Low-dose intravenous tirofiban is superior to intravenous aspirin in avoiding in-stent thrombosis in patients undergoing MT plus carotid stenting in the setting of AIS due to TL. Methods: The ATILA-trial is a multicenter, prospective, phase IV, randomized, controlled (aspirin group as control), assessor-blinded clinical trial. Patients fulfilling inclusion criteria (AIS due to TL, ASPECTS ⩾ 6, pre-stroke modified Rankin Scale ⩽2 and onset <24 h) will be randomized (1:1) at MT onset to experimental (intravenous tirofiban) or control group (intravenous aspirin). Intravenous aspirin will be administered at a 500 mg single dose and tirofiban at a 500 µg bolus followed by a 200 µg/h infusion during first 22 h. All patients will be followed up to 3 months. Sample size estimated is 240 patients. Outcomes: The primary efficacy outcome is the proportion of patients with carotid in-stent thrombosis within the first 24 h after MT. The primary safety outcome is the rate of symptomatic intracranial hemorrhage. Secondary outcomes include functional independence defined as modified Rankin Scale 0–2, proportion of patients undergoing rescue therapy due to in-stent aggregation during MT and carotid reocclusion at 30 days. Discussion: ATILA-trial will be the first clinical trial regarding the best antiplatelet therapy to avoid in-stent thrombosis after MT in patients with TL. Trial registration: NCT0522596.